Creating a proactive interdisciplinary approach to care: Embedding oncology care coordination within an oncology patient and family support program. Issue 28 (1st October 2022) - Low, Sarah; Nakaji, Ayaka; Irwin, Scott A; Van der Gaag, Jan-Kees
Abstract : 51 Background: The benefits of providing psycho-oncology services have been well documented in producing better effective team collaboration, patient outcomes, and reduced healthcare utilization. Cedars-Sinai Cancer spans five locations and serves over 11, 000 patients a year. Their robust Patient and Family Support program (PFSP) includes psychiatry, palliative medicine, social work, nutrition, cancer rehabilitation, survivorship, and chaplaincy to envelop patients in multiple dimensions of support. A new oncology care coordination (CC) model embedded a social work (SW) and nurse (RN) CC within PFSP to identify and meet diverse unmet needs of patients through close interdisciplinary collaboration. Methods: Oncology CC was established within PFSP, containing an oncology SW CC and an oncology RN CC. Patients with higher acuity needs were identified through multiple avenues such as: health plan reporting and dashboards in the electronic medical record (EMR) providing alerts for patients with unmet needs. Preliminary data was captured on interdisciplinary collaboration and care coordination from a daily log kept by coordinators, as well as from the EMR. Results: Over 6 months (9/2021 to 2/2022), the PFSP CC team served 688 patients providing 1280 interventions. Of the 1280 interventions, 22% were coordination with other PFSP services; of which 54% was with SCM, 36% with Clinical SW, and 18% represented new referrals. 13% focused on outside services including medical devices, home health, and community resources. 6% comprised of post-discharge calls by the RN CC and 16% represented direct SW CC outreach. Care coordination such as appointment scheduling, assistance with prescriptions and communication with medical teams represented 9%, 1% and 11% of the interventions respectively. Conclusions: Results demonstrated for this subset of patients that the highest needs of oncology PFSP CC were SW and SCM, to address needs such as pain and symptom management, goals of care conversations and community resource linkage. Anecdotally, communication with primary oncology and other medical teams proved to be an essential role of the CC team, particularly to address inpatient to outpatient transitions of care. Discussion: CC team involvement is time-limited and appears to rely on the long-term relationship patients have with PFSP interdisciplinary team members for interventions to be long-lasting and effective. The CC team leveraged existing relationships that PFSP providers had established with primary oncology teams, allowing for timely care coordination. Future goals include: 1) developing an algorithm to better identify patients with higher acuity and unmet needs; 2) measuring impacts of CC services on care outcomes, health care utilization and reduced symptom burden; 3) expanding the CC team to serve more of the patient population.